Evaluating Influencing Factors of Audiences’ Attitudes toward Virtual Concerts: Evidence from China - Jing Deng; Younghwan Pan (Behavioral Sciences, 2023)
The purpose of this study is to investigate and validate the influencing factors of audiences’ attitudes toward virtual concerts. In order to address this issue, the current study proposes a conceptual model integrating player experience factors (autonomy, relatedness, and engagement) and the technology acceptance model (perceived usefulness, perceived ease of use, and perceived enjoyment). An online questionnaire on virtual concert experiences was conducted among Chinese audiences who had attended virtual concerts previously. Structural equation modeling was then used to establish the relationships between variables. The results suggested that autonomy, relatedness, and engagement positively impacted perceived usefulness, perceived ease of use, and perceived enjoyment. Furthermore, the perceived usefulness, perceived ease of use, and perceived enjoyment were significant predictors of audiences’ attitudes. The findings of this study could provide a reference for relevant virtual entertainment providers and could also serve as a point of development and exploration for the technology acceptance model and player experience in the field of virtual concerts.